The art of film magic 20 years of Weta - Jackson, Peter 1961- (Harper Design, 2014)
This deluxe slipcased two-volume set is an insider's tour of twenty years of film-making magic at Weta Workshop and Weta Digital, the creative companies behind such celebrated films as The Lord of the Rings, Avatar, The Avengers, King Kong, District 9 and The Hobbit. Based in Wellington, New Zealand, these two companies, founded by Peter Jackson, Jamie Selkirk, Tania Rodger and Richard Taylor have been an integral part of some of the most ground-breaking and acclaimed movies of all time
Title from slipcase
Keywords: Weta Workshop; Weta Workshop -- Firma; Animation (Cinematography); Digital cinematography; Cinematography / New Zealand; Cinematography; Film; Spezialeffekt; New Zealand